'Oxford in the bush': the founding (and diminishing) ethos of Rhodes University. (2nd January 2016) - Maylam, Paul
ABSTRACT: Over the years, many members of the Rhodes University community have proudly claimed their university to be a kind of transplanted Oxford, while others have viewed this claim as pretentious – hence the derogatory label 'Oxford in the bush'. This article explores the connections and comparison between the two institutions. In the early twentieth century, both universities strongly identified with the British imperial cause; and for decades Rhodes University regularly celebrated its symbolic association with the historical figure of Cecil Rhodes, who also happens to be one of the most commemorated figures in Oxford. There was also a shared ethos, as both laid stress on a style of education that was character-building, a prerequisite for which was a strong grounding in the classics. There was, too, a cultural affinity between Rhodes and Oxford, exemplified in the strict segregation of the sexes, the importance attached to sporting achievement, and a tendency to engage in frivolous activities. The article goes on to show how over time the Oxford tradition at Rhodes came to be challenged and undermined, especially from the late 1960s onwards.